The Effect of Intelligence on Financial Development: A Cross-Country Comparison - Oasis Kodila-Tedika; Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
We assess the correlations between intelligence and financial development in 123 countries using data averages from 2000-2010. Human capital is measured in terms of IQ, cognitive ability & cognitive skills, while financial development is appreciated both from financial intermediary and stock market development perspectives. Short-term financial measures are private and domestic credits whereas long-term financial indicators include: stock market capitalization, stock market value traded and turnover ratio. The following findings are established. (1) With respect to private credit, the positive correlations of IQ and cognitive ability are broadly similar while that of cognitive skills is substantially higher in terms of magnitude. (2) The correlation between intelligence and other financial variables are broadly similar. (3) The underlying findings are broadly confirmed in terms of sign of correlation, though the magnitude of correlation is higher (lower) with the addition of social capital or ethnic fractionalization (institutions or income). (4) When continents are excluded to control for extreme effects, baseline results are confirmed and the following on order of continental importance in financial development is established in increasing magnitude: Africa, Americas, Oceania, Europe & Asia.
Keywords: E01; G20; I20; I29; 330; Financial development; Intelligence; Skill; Human Capital